Trends in Prescribing Patterns and Drug Related Problems of Kidney Disease Patients - Muhammad Arfat Yameen; Mubashra Tafseer; Warda Khan; Sanaa Anjum; Raza-E-Mustafa; Ossam Chohan (Journal of the Pakistan Medical Association, 2021)
Objective: The aim of the study was the evaluation of drug-related problems, including drug-drug interactions, dose error, use of nephrotoxic drugs and polypharmacy with special emphasis on kidney disease patients. Methods: Descriptive cross-sectional study from January to April 2019 was carried out in nephrology ward of Ayub teaching hospital, Abbottabad, Pakistan to review patient’s medication orders for evaluation of drug-related problems. Doses of medicine and drug-drug interactions were evaluated by comparing it with standard protocols given in BNF and Lexicomp software. Prescriptions were also evaluated for polypharmacy and use of nephrotoxic drugs. Results: Out of 131 patients, majority were males 72 (55%). Drug-drug interactions were found in 69 (52.7%) patients among which the highest percentage was of the moderate drug-drug interaction (48.1%) followed by major and minor drug-drug interaction (29.8% and 20.6% respectively). Incidence of polypharmacy (51.9%) and use of nephrotoxic drug (77%) was high while dose error was low up to 10.7%. All the drug-related problems were present with a high percentage in patients with CKD as compare to other kidney diseases. There was significant association of CKD stages with DDIs, polypharmacy, dose error and prescribing drugs. There was significant positive correlation among DDIs-polypharmacy and prescribing drugs was noted in the study. Conclusion: The higher incidence of drug-related problems in our study setting reflects irrational prescribing trends and deficiency of professional staff dealing kidney disease patients. Key Words: kidney disease, drug-drug interactions, polypharmacy, nephrotoxic drugs, dose error. Continuous...